Research in organizational change and development. Vol. 24 - Noumair, Debra Ann; Shani, Abraham B. (Emerald, 2016)
Highlights include a reflection on forty years of collaboration and provides an inside perspective on collegial partnerships; the first recipients of the Pasmore-Woodman Award (AOM 2015) consider personal recollections as well as general principles about successful academic partnerships; one of the first women in the field provides a perspective on the interdependence of research and practice through a gender lens; while reflecting on the role of women in ODC across a fifty-year time period; strategies for managing changes in the research question when conducting field-based action research advances our understanding of evidence-based practice through the application of theory; Dialogic OD, a relatively new perspective in the field, is explored by discussing a case in which social space serves as transitional space and the ODC practitioner is provided a theoretically informed set of principles that can be applied and evaluated across contexts; the nature and role of organization identity shades new insights about the potential impact of organization development work on company culture and effectiveness; the challenges of integrating business strategy and organization development in the fast changing newspaper industry.
Keywords: Business & Economics -- Organizational Behavior.; Organizational theory & behaviour.; Organizational change.; elektronické knihy; electronic books